Un text excèntric. L'Ambaixada de Francesc Fontanella. - VALSALOBRE, PEP (Scripta, 2023)
Following a preamble that provides a summary of the abundant and diverse questions raised by this text penned by the Barcelona baroque poet Francesc Fontanella -which cover all aspects: its transmission in manuscripts, testimonies with divergent texts, authorship, creative context, literary genre- a response is offered for each based on the last (few) contributions that have been made on the issue together with new approaches by the author to the work. A hypothesis of the work's context and its dramatic execution is then ultimately established. This introduction serves as a presentation of the critical edition of the text with exhaustive annotations. The Annex includes all elements pertaining to textual criticism of the work arranged for the consideration of the reader and researcher.